Towards telehealth : an online diagnosis system for trail making test remove - Kwek, Ai Hui (2017)
With the increasing number of dementia cases globally and in Singapore, the need for long term care for people with this illness is necessary. The illness is an irreversible and progressive brain disease that slowly destroys the memory and thinking abilities. Scientists do not yet have the answer to cure dementia but research has shown that people who maintain active cognition could delay the symptoms of the disease. Trail-Making-Test (TMT) is one of the most clinically useful neuropsychological tests and is used routinely in the diagnosis of many neurological conditions. It consists of two parts, TMT-A & TMT-B. It requires the player (patient) to perform an action of connecting-the-dots by drawing a single line through 25 circles that are randomly distributed. Both parts of the TMT require sensorimotor ability, working memory, and set-switching ability. Comparing an individual’s performance on the two parts of the Trail Making Test is considered to be helpful in examining the integrity of higher cognitive functioning. The aim of this project is to create a web application to ensure the patients are being monitored closely and timely through the TMT test cases. The doctors would give their evaluation based on the patients’ TMT test cases. The test cases’ data would be taken from players’ (patients) game results in the mobile application. The data would then be plotted into the web application for the doctors to view and to make an evaluation. A focus group study was conducted to assess this project qualitatively. The results gathered from this assessment were significant and positive, reflecting the potential that this project have in improving patients’ access to the mental health providers and vice versa. It also increases the efficiency of the doctors and eases the problem of shortage of health care professionals.